Visions in the Ville: Looking toward the next 125 years. Volume 1: Critical maps - Hahn, Howard D.; Belanger, Blake (Kansas State University. College of Architecture, Planning & Design, Department of Landscape Architecture and Regional & Community Planning, 2014)
The 2014 “Visions in the Ville” summer studio explored Aggieville’s potential as the community looks toward the future. The studio spanned eight weeks and was offered by the Department of Landscape Architecture and Regional & Community Planning at Kansas State University. Associate Professors Blake Belanger and Howard Hahn directed the efforts of fourteen mid-level graduate landscape architecture students, and documented the studio’s research and design findings in two volumes: Volume 1: Critical Mapping and Volume 2: Design Proposals. The intent of the studio was to identify ideas, visions, and strategies that will contribute to a community dialogue about enhancing Aggieville’s future. The studio researched the history, character, economics, demographics, and ecological conditions of Aggieville, as well as the district’s broader role in the evolving community and regional context. Volume 1 documents more than 100 maps generated by the studio through “Critical Mapping,” an iterative design process consisting of community engagement, research, strategic design, argumentation, and communication. More than simply gathering and mapping information, Critical Mapping seeks to classify, correlate, and compare site information across a broad spectrum of topics for identifying dilemmas/opportunities and design strategies. Findings in volume 1 include on-site inventory of existing conditions, analysis of geospatial, economic, demographic, and social data, evaluation of current conditions, and strategies for accomplishing community and planning goals.
Keywords: Kansas State University; Aggieville, Manhattan; Landscape architecture; Urban design; Critical mapping